HEDONIC VALUE DAN UTILITARIAN VALUE TERHADAP CUSTOMER SATISFACTION SERTA DAMPAKNYA TERHADAP BEHAVIOR INTENTIONS - MIRANTI WIDYA PRAMITA; AULIA DANIBRATA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The purpose of this research is to examine the effect of hedonic value and utilitarian value impact to behavioral intentions of Customer Bandar Djakarta Bekasi and survey at Bekasi city. The research design used in this research is causality and descriptive research. The sampling in this research was purposive sampling, and uses 255 respondents around Bekasi city. Data for this study is used the primary data where the quetionnaire spreaded to respondents. The methods for the data analysis is structural equation model. The result on this research is hedonic value has not impact to customer satisfaction. Utilitarian value has impact to customer satisfaction. Hedonic value has impact to behavioral intentions. Utilitarian value has not impact to behavioral intentions. Customer satisfaction has impact to behavioral intentions